Persistent hyperglycemia worsens the oleic acid induced acute lung injury in rat model of type II diabetes mellitus - Rinkoo Yadav; Vikas Kailashiya; Hanjabam B Sharma; Ratna Pandey; Priyanka Bhagat (Wolters Kluwer Medknow Publications, 2023)
Aim: This research aimed to study the impacts of persistent hyperglycemia on oleic acid (OA)-induced acute lung injury (ALI) in a rat model of type II diabetes mellitus. Materials and Methods: Healthy adult male albino rats that weigh 150 to 180 g were divided into four groups (n = 6). Group I-saline (75 μL i.v.) was injected and served as a control; group II-OA (75 μL i.v.) was injected to induce ALI. Group III-pretreated with a high-fat diet and streptozotocin (35 mg/kg), was injected with saline, and served as a control for group IV. Group IV was pretreated with a high-fat diet, and streptozotocin (35 mg/kg) was injected with OA (75 μL i.v). Urethane was used to anesthetize the animal. The jugular venous cannulation was done for drug/saline administration, carotid artery cannulation was done to record blood pressure, and the tracheal cannulation was done to maintain the respiratory tract's patent. Heart rate, mean arterial pressure, and respiratory frequency were recorded on a computerized chart recorder; an arterial blood sample was collected to measure PaO2/FiO2. Additionally, the pulmonary water content and lung histology were examined. Result: Hyperglycemic rats showed no significant change in the cardio-respiratory parameter. Histology of the lungs shows fibroblastic proliferation; however, rats survived throughout the observation period. There was an early deterioration of all the cardio-respiratory parameters in hyperglycemic rats when induced ALI (OA- induced), and survival time was significantly less compared to nonhyperglycemic rats. Conclusion: Persistent hyperglycemia may cause morphological changes in the lungs, which worsens the outcome of acute lung injury.